Pelatihan dan Pembimbingan Khat Al-Qur’an sebagai Upaya Meningkatkan Kemampuan Siswa di Maluku Tengah dalam Mengikuti MTQ Provinsi Maluku - Arfa, Arman Man (Jurnal Pengabdian Arumbai, 2023)
Community service activities in preparation for students to take part in the Maluku Province MTQ competition have been successful. It understands students about the art of Khat Al-Qur'an and improves Khat writing skills. It also promotes a deep understanding of the Qur'an, improves social relationships, and identifies individual talents and potential. The Khat Al-Qur'an competition in MTQ is not only visual art, but also an expression of love and respect for the messages of the Al-Qur'an, creating space for spiritual reflection. The main aim is to increase understanding of the Al-Quran and the art of Khat Al-Qur'an and prepare students to be successful in the Maluku Province MTQ competition, while also promoting religious values. This service aims to improve students' skills in the art of Khat Al-Qur'an, prepare for success in MTQ Maluku Province, deepen understanding of the Al-Quran, and develop students' individual abilities. This activity was carried out on 11 to 15 October 2023 at SMP Negeri 87 Central Maluku. Implementation of this activity uses the Asset Based Community Development (ABCD) method. The service activities successfully prepared students for MTQ Maluku Province by deepening their understanding of the art of Khat Al-Qur'an and improving their writing skills through intensive training and regular evaluations.